La prórroga de jurisdicción como cláusula abusiva en los contratos de tiempo compartido, en el derecho argentino - Estigarribia Bieber, María Laura (2004)
According to the present reality, we can say without doubts that the so called “time shared contracts” constitute the catalogue of contracts wich adhere to the general conditions or clauses predetermined by the supplier or entrepreneur respect to the consumers. These contracts, due to their structure and the nature of their parts, have to be considered as real consumption contracts, being regulated in most of the world laws by specific rules aimed to the Consumer Protection. This paper intends to base its central idea on the fact that in this kind of contracts the control of the content of the predetermined conditions must lead to the declaration of nullity of those conditions imposing modifications of the natural territorial jurisdiction. These modifications must be conceived as abusive clauses since they imply a restriction to the consumer’s fundamental rights of “defense on trial and access to court” which have a constitutional hierarchy. All this idea is based on the regulation frame given by the Argentina private law.